2018
DOI: 10.3382/ps/pey249
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota correlates with fiber and apparent nutrients digestion in goose

Abstract: To explore the relationship among the level of fiber, gut microbiota, and nutritional substances, we applied the next generation sequencing technology for the identification of the composition and structure of microbiota in the gastrointestinal tract. In this study, a total of 25 phyla and 298 genera were identified from the gastrointestinal tract; Firmicutes, Bacteroidetes, and Proteobacteria were the predominant phyla. The ability of cecum in carbohydrate metabolism was significantly higher than that of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
4
14
0
1
Order By: Relevance
“…As previously described in domesticated geese [15,[35][36][37], and in birds in general [38], Firmicutes and Proteobacteria (> 70% of sequences in all groups) were the two main phyla in the Greylag goose (Anser anser) ileal microbiota. Microbial composition did however strongly differ according to the steatosis induction system.…”
Section: Discussionsupporting
confidence: 73%
“…As previously described in domesticated geese [15,[35][36][37], and in birds in general [38], Firmicutes and Proteobacteria (> 70% of sequences in all groups) were the two main phyla in the Greylag goose (Anser anser) ileal microbiota. Microbial composition did however strongly differ according to the steatosis induction system.…”
Section: Discussionsupporting
confidence: 73%
“…As an important part of the body, the gut microbiota plays vital roles in feed digestion ( Yang et al., 2017 , Liu et al., 2018 ), nutrition absorption ( Krajmalnik-Brown et al., 2012 , Semova et al., 2012 ), energy extraction ( Turnbaugh et al., 2006 , Heiss and Olofsson, 2018 ), immune response ( Furusawa et al., 2013 , Takiishi et al., 2017 ), and disease resistance ( Mazmanian et al., 2008 , Smith et al., 2013 ). Previous reports have shown that the gut microbial composition can be altered by various factors such as environmental temperature ( Fontaine et al., 2018 ), diet ( David et al., 2014 ), age ( O'Toole and Jeffery, 2015 ), disease ( McKenzie et al., 2017 ), and drugs ( Modi et al., 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the abundances of Proteobacteria and Kiritimatiellaeota in the cecum were significantly higher in the LRS, while the abundance of Bacteroidetes in the cecum was significantly higher in the NRS (Figure 5A), whereas these phyla showed no difference in the duodenum between the two housing systems. The role of Proteobacteria in apparent nutrient digestion has been frequently been reported to be associated with cellulose activity (30), while Kiritimatiellaeota is a newly described phylum, and little is known about its members. Spring et al (31) showed that Kiritimatiella glycovorans L21-Fru-ABT fermented xylose to ethanol and acetate but was not able to utilize starch, sucrose, or fructose.…”
Section: Discussionmentioning
confidence: 99%